PELATIHAN PENERAPAN METODE SNOWBALL THROWING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS I SD NEGERI 014 RAMBAH SAMO - Rinja Efendi; Elvina; Hasrijal; Abdul Putra Ginda Hasibuan; Dorisno (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Rokania, 2025)
The training on the application of the Snowball Throwing method was carried out as an effort to improve the speaking skills of grade I students at SD Negeri 014 Rambah Samo. Based on the results of initial observations, students' speaking skills are still low, which is caused by a lack of variety of learning methods and a lack of training for teachers. The Snowball Throwing method was chosen because of its cooperative, interactive, and fun nature, so it can encourage active student participation. The training activities were carried out in three sessions in September 2024 with the participation of 23 students. The results of the implementation showed an increase in speaking skills and enthusiasm from both students and teachers. Despite the challenges in the first meeting, the improvement in strategy in the next session showed positive results. This training has proven to be effective in improving students' communication skills and teachers' understanding of the application of innovative methods in learning.